KEBIJAKAN PEMBERIAN PENDIDIKAN KARAKTER DALAM PROSES PEMBENTUKAN SARJANA ADMINISTRASI PUBLIK DI FISIP UNDIP - Marom, Aufarul (JURNAL ILMU SOSIAL, 2014)
The concept of character education has been implemented in school and campus since long time ago, but the result is not so good.The Policy of character education provision for new students began the school year 2012/2013 , then continued in 2013/2014 was motivated by the policy of the University . The University considers that new students need to be equippedÂ  moral values that are expected to form the character of students and change their mindset from properties that are not commendable as , inappropriate character , denied when ordered , lack of discipline etc. Shape the implementation of character education provision in order to establish a Public Administration graduate be material submitted by the faculty and the games were hosted by students , coordinated by HMJ and Senate and BEM. There are several factors that support the successful delivery of character education: The support of the faculty , faculty staff and students themselves , infrastructures facilities , LCD, air conditioning , loudspeakers , material factors , the game . The other hand, there are some factors hamper as not all the facilities function properly , the absence of strict sanctions for those who do not participate , also for those who are not active, which is not optimal coordination factor, the perception by some students who think character education is just playing games , not compulsory lessons or lectures etc.